2017
DOI: 10.1007/s11105-017-1032-4
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Tolerant Brassica rapa Shows Rapid Expression of Gene Networks for General Stress Responses and Programmed Cell Death Under Simulated Drought Stress

Abstract: Production of oilseed rape/canola (Brassica napus) is increasingly threatened by dry conditions while the demand for vegetable oil is increasing. Brassica rapa is a genetically diverse ancestor of B. napus, and is readily crossed with B. napus. Recently, we reported promising levels of drought tolerance in a wild type of B. rapa which could be a source of drought tolerance for B. napus. We analysed global gene expression by messenger RNA sequencing in seedlings of the drought-tolerant and a drought-sensitive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 86 publications
(104 reference statements)
1
25
0
Order By: Relevance
“…B. rapa is distributed widely on a global scale 2 Plant Phenomics with the centre of origin in the Old World and centres of diversity in Asia [10][11][12][13][14], with some types flourishing in heat and drought-affected regions [15]. Genotypic variation for heat and drought resistance has been reported recently in B. rapa [16,17], and a tolerant genotype responded to simulated drought with rapid expression of gene networks for general stress responses and programmed cell death [18].…”
Section: Introductionmentioning
confidence: 99%
“…B. rapa is distributed widely on a global scale 2 Plant Phenomics with the centre of origin in the Old World and centres of diversity in Asia [10][11][12][13][14], with some types flourishing in heat and drought-affected regions [15]. Genotypic variation for heat and drought resistance has been reported recently in B. rapa [16,17], and a tolerant genotype responded to simulated drought with rapid expression of gene networks for general stress responses and programmed cell death [18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, these studies found that JA is required for resistance, indicated by susceptibility in mutants with non-functional copies of genes involved in the JA pathway, including a mutation in the downstream COI1 gene (see Glazebrook 2005 for further details). Additionally, a recent B. rapa expression study was used to identify candidate drought response genes (Guo et al, 2017).…”
Section: Plant-pathogen Systemmentioning
confidence: 99%
“…We next considered 7,076 genes candidate drought response genes (Additional le 3) which were differentially expressed in Guo et al (2017) study in response to a polyethylene glycol (PEG) treatment, as compared to controls (no PEG), and that had a >2 fold change at 12 hours post-treatment. We then identi ed genes differentially expressed in common among both this drought study and the NFPR studies (above).…”
Section: Functional Analysismentioning
confidence: 99%
“…To study the expression pattern of BrGRP genes under drought stress, the transcriptome data of Chinese cabbage (CR2355 and ATC92037) were also analyzed [29]. CR2355 is a root transcriptome data of drought-tolerant (DT) material which can keep the required biomass for mature when suffered from transient drought stress during the reproductive phase, while ATC92037 is a root transcriptome data of drought-sensitive (DS) material which showed a significant reduction in biomass after transient drought stress.…”
Section: Expression Profiling Of Brgrps Under Drought Stressmentioning
confidence: 99%
“…The expression differences of BrGRP genes under biotic and abiotic stress were also analyzed based on the transcriptome data of Chinese cabbage under high temperature at 45 ℃ [27], low temperature at 4 ℃ [28], drought [29], soft rot stress [30]. The expression levels of BrGRP genes were calculated with the Fragments Per kb per Million reads (FPKM) values [55] and displayed with cluster heat map drawn by TBtools [52].…”
Section: Expression Pattern Analysis Of Brgrp Genesmentioning
confidence: 99%